Transforming employment: The AI & Automation era - Bajpai, Anuj; Tiwari, Shreyansh (Journal of Social Review and Development, 2025)
The rapid combination of artificial intelligence (AI) and automation technologies is driving significant changes in the labor market, requiring a re-evaluation of traditional employment models. This paper look into the great effects of these technologies, focusing on both job displacement and the creation of new job opportunities. It explores the evolving skills needed for the future workforce, highlighting the increasing importance of adaptability, critical thinking, and digital literacy. The study also looks at the economic impacts, weighing potential productivity improvements against the risk of deepening income inequality. Ethical concerns, such as algorithmic bias, data privacy, and the broader social consequences of automation, are also explored. Additionally, the paper emphasizes the need for comprehensive policy frameworks and educational reforms to mitigate the adverse effects of job loss and facilitate a smooth transition. Dynamic solutions like retraining programs, continuous learning opportunities, and the possible introduction of universal basic income are discussed as ways to build a resilient and inclusive job market. By reviewing current research and trends, this paper calls for collaboration between policymakers, businesses, and educational institutions to tackle the challenges produce by AI and automation, and to ensure that the future of work is productive and fair for all.